2014 International Conference on Advances in Computing, Communications and Informatics (ICACCI) 2014
DOI: 10.1109/icacci.2014.6968373
|View full text |Cite
|
Sign up to set email alerts
|

Image compression scheme based on zig-zag 3D-DCT and LDPC coding

Abstract: The prime necessity in communication system is utilizing the available bandwidth efficiently. Hence, compression of data to be sent over the link has become inevitable. In this paper, an algorithm for compressing hyperspectral space images based on ZigZag 3D-DCT (Discrete Cosine Transform) technique is proposed. This method converts 2D gray-scale images into a 3 dimensional cube formation of 8*8*8 pixels and is operated with DCT. Thereafter the quantization and zig-zag scanning processes are implemented. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Table I provides the time required for segmenting the image according to user input and assigning the cluster heads accordingly. It is observed that the, parallel processing and clustering improves the processing time compared to [9,10]. However, as the number of segments increases the complexity in assigning the cluster heads increases which in turn results into the excessive amount of time consumption and hence degrades the performance of the algorithm.…”
Section: A Analysis Of Processing Time Of the Algorithmmentioning
confidence: 90%
See 3 more Smart Citations
“…Table I provides the time required for segmenting the image according to user input and assigning the cluster heads accordingly. It is observed that the, parallel processing and clustering improves the processing time compared to [9,10]. However, as the number of segments increases the complexity in assigning the cluster heads increases which in turn results into the excessive amount of time consumption and hence degrades the performance of the algorithm.…”
Section: A Analysis Of Processing Time Of the Algorithmmentioning
confidence: 90%
“…The quality parameters for various images have been evaluated. It is observed that the, parallel processing and clustering improves the processing time without hampering the quality of image compared to [9,10].…”
Section: A Analysis Of Processing Time Of the Algorithmmentioning
confidence: 92%
See 2 more Smart Citations
“…The algorithm performs better than the algorithm illustrated in various papers such as[3][4][5][6].Fig.10illustrates the PSNR denouement between original with respect to recovered color image, considering two cases; viz. 2-level Sub-band replacement method and 4-level Subband replacement method.…”
mentioning
confidence: 92%